Design and implementation of magnetron power supply and emulator - Abodhir, Nourdeen; Watson, Alan James; Ji, Chao; Clare, Jon C. (2016)
The paper presents a novel resonant based high performance power converter solution for industrial magnetron systems. Based the characteristics of the magnetron, an emulator prototype is also proposed to represent the magnetron load behaviour in a laboratory environment. A detailed design and implementation procedure is presented, including the design and control of the resonant power converter, together with the magnetron emulator in practical aspects. Experimental results are provided in order to demonstrate the feasibility of the proposed converter and emulator.